INTERNATIONAL CRIMINAL COURT: SPECIFIC CHARACTER AND CONTRADICTIONS OF JURIDICAL REGIME - N. V. Dremina-Volok (Russian Journal of Economics and Law)
The article is devoted to the disclosing of meaning of international criminal court activity. The author considers separate situations when international criminal court made decisions on questions concerning in jurisdiction.